The integration of close range photogrammetry and database management for traffic accident mapping [electronic resource] - Nurkhaliesa Balqis Hamzah, 1987- (2014)
Thesis (Sarjana Sains (Kejuruteraan Geomatik)) - Universiti Teknologi Malaysia, 2014